2019
DOI: 10.1108/aaaj-07-2017-3044
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dynamics of SER evolution: an institutional understanding

Abstract: Purpose The purpose of this paper is to provide a theoretically informed analysis of social and environmental reporting (SER) evolution, i.e. how and why the SER evolved over time in a cooperative bank in Italy. Design/methodology/approach The paper is based on a qualitative fieldwork case study conducted from 2011 to 2015. Information and data were collected through several methods including: interviews with managers involved in the SER’s process; analysis of the SER-related documents; analysis of the websi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 55 publications
(162 reference statements)
1
26
0
2
Order By: Relevance
“…Drawing on institutional studies, accounting researchers have demonstrated how logics shape organizational responses (Safari et al, 2020;Golyagina, 2020;Yee, 2020;Conrath-Hargreaves and W€ ustemann, 2019). Yet, as Contrafatto et al (2019) note, relatively little attention has been paid to the likelihood that logics drive accounting practices, including sustainability reporting. More specifically, accounting researchers have paid little attention to how loosely defined institutional arrangements, unclear institutional rules and sharp contestation between logics in an emerging field may drive greater practice variation at the organizational level (Vican and Pernell-Gallagher, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on institutional studies, accounting researchers have demonstrated how logics shape organizational responses (Safari et al, 2020;Golyagina, 2020;Yee, 2020;Conrath-Hargreaves and W€ ustemann, 2019). Yet, as Contrafatto et al (2019) note, relatively little attention has been paid to the likelihood that logics drive accounting practices, including sustainability reporting. More specifically, accounting researchers have paid little attention to how loosely defined institutional arrangements, unclear institutional rules and sharp contestation between logics in an emerging field may drive greater practice variation at the organizational level (Vican and Pernell-Gallagher, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Channuntapipat et al, 2019;Cerbone and Maroun, 2019). However, the link between motives and practice variations remains poorly understood in the sustainability literature, both theoretically and empirically (Contrafatto et al, 2019). This paper fills this gap.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Relevant questions for this time period include who produces the innovations (and how they do this), how these innovations differ from existing norms and practices, and how new practices create new networks. Institutional entrepreneurs have been studied for the social reporting of a cooperative bank by Contrafatto et al (2019), for environmental reporting in the UK and Spain by Bebbington et al (2012) and for SR by Levy et al (2010). The notion of institutional entrepreneurship is consistent with the argument that the different steps in institutional inscription are characterized by power, struggle and negotiation that involve multiple actors and their interests (Djelic and Sahlin-Andersson, 2006).…”
Section: The Dynamics Of Institutionalization: the Life-cycle Of Sr Normsmentioning
confidence: 99%
“…It was, first of all, necessary to explore the institutional and organizational context of the HUB, to examine the sustainability implementation process within its accounting practices (Contrafatto, 2014). As institutional research has pointed out, the characteristics of the context can enable or complicate involvement in sustainability reporting (Contrafatto et al , 2019) and, as a result, the dynamics and the processes of implementation (in this case the implementation of sustainability) will be context-dependent (Modell, 2014). An analysis of the context in which HUB operates is, therefore, provided in the following section.…”
Section: Implementation Of Sustainability In Hub Accounting Practicesmentioning
confidence: 99%